El ensamble musical: estrategia metodológica para la inclusión de una población neurológicamente diversa: Estrategia metodológica para la inclusión de una población neurológicamente diversa (2022)
The musical ensemble is a methodological strategy that generates an inclusive and collaborative environment within an institution. Result of a qualitative research, the article aims to analyze the research challenges generated by the actions in action research with six students diagnosed with disabilities and belonging to the inclusive music program of the Municipal School of Arts and Crafts of Bucaramanga (EMA), with whom it was possible to intervene their practices and limitations through a musical ensemble, with which the inclusive process of students and their families was impacted. The conclusions reiterate that the investigation of the skills of the participants and the implementation of the didactic sequence designed, the students were able to develop the necessary skills to assume the assembly of two musical arrangements worked on this proposal and be part of an inclusive musical ensemble, the which was integrated into the annual results of the EMA.